2013
DOI: 10.3390/e15010372
|View full text |Cite
|
Sign up to set email alerts
|

Is Encephalopathy a Mechanism to Renew Sulfate in Autism?

Abstract: This paper makes two claims: (1) autism can be characterized as a chronic lowgrade encephalopathy, associated with excess exposure to nitric oxide, ammonia and glutamate in the central nervous system, which leads to hippocampal pathologies and resulting cognitive impairment, and (2), encephalitis is provoked by a systemic deficiency in sulfate, but associated seizures and fever support sulfate restoration. We argue that impaired synthesis of cholesterol sulfate in the skin and red blood cells, catalyzed by sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 214 publications
(235 reference statements)
0
15
0
Order By: Relevance
“…We have recently proposed that autism can be characterized as a chronic low-grade encephalopathy, where the cascade of events taking place in the brain is a process that enables the renewal of severely depleted sulfate supplies to the brain [277]. We identified a dysbiosis in the gut as a source of ammonia that initiates the encephalytic response, and we proposed glyphosate as one of the many environmental toxins that might be responsible for the dysbiosis and for sulfate depletion.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently proposed that autism can be characterized as a chronic low-grade encephalopathy, where the cascade of events taking place in the brain is a process that enables the renewal of severely depleted sulfate supplies to the brain [277]. We identified a dysbiosis in the gut as a source of ammonia that initiates the encephalytic response, and we proposed glyphosate as one of the many environmental toxins that might be responsible for the dysbiosis and for sulfate depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Many potential triggers have been investigated for a causal role in ASD disorders, including sulfate levels [87], serotonin levels [88], pesticide exposure [89], maternal trauma [90], aluminum and acetaminophen [91], oxytocin [92], general diet [11], and mercury poisoning [93]. Most of these studies have demonstrated significant correlations; however, the fact that so many separate factors have a significant role in the development of a set of symptoms, suggests underlying factors may be at play.…”
Section: Potential Triggers Of Asdmentioning
confidence: 99%
“…up to 100,000-fold lower than those found in antiperspirants, and in the range of those recently measured in the human breast, results in loss of contact inhibition and anchorage-independent growth. This finding should serve as a sentinel warning that environmental Al exposures [252] from dietary [300], parenteral [301], and topical sources [302], may have oncogenic [299,303] and epigenetic [245,253] consequences.…”
Section: Breast Cancermentioning
confidence: 99%